A passive upper-limb exoskeleton reduced muscular loading during augmented reality interactions. (May 2023) - Kong, Yong-Ku; Park, Sang-Soo; Shim, Jin-Woo; Choi, Kyeong-Hee; Shim, Hyun-Ho; Kia, Kiana; Kim, Jeong Ho
Abstract: The aim of this study was to evaluate a passive upper-limb exoskeleton as an ergonomic control to reduce the musculoskeletal load in the shoulders associated with augmented reality (AR) interactions. In a repeated-measures laboratory study, each of the 20 participants performed a series of AR tasks with and without a commercially-available upper-limb exoskeleton. During the AR tasks, muscle activity (anterior, middle, posterior deltoid, and upper trapezius), shoulder joint postures/moment, and self-reported discomfort were collected. The results showed that the exoskeleton significantly reduced muscle activity in the upper trapezius and deltoid muscle groups and self-reported discomfort. However, the shoulder postures and task performance measures were not affected by the exoskeleton during the AR interactions. Given the significant decrease in muscle activity and discomfort without compromising task performance, a passive exoskeleton can be an effective ergonomic control measure to reduce the risks of developing musculoskeletal discomfort or injuries in the shoulder regions. Highlights: Musculoskeletal load associated with AR interactions were characterized. The effects of an exoskeleton on musculoskeletal load were evaluated during AR tasks. The results indicate an exoskeleton can reduce shoulder strain during AR interactions.